Augmented T1‐weighted steady state magnetic resonance imaging. (28th March 2022) - Ye, Yongquan; Lyu, Jingyuan; Hu, Yichen; Zhang, Zhongqi; Xu, Jian; Zhang, Weiguo; Yuan, Jianmin; Zhou, Chao; Fan, Wei; Zhang, Xu
Abstract : T1 contrasts obtained using short‐TR incoherent steady state gradient echo (GRE) methods are generally suboptimal, to which non‐T1 factors in the signals play a major part. In this work, we proposed an augmented T1 ‐weighted (aT1 W) method to extract the signal ratio between routine GRE T1 W and proton density‐weighted signals that effectively removes the non‐T1 effects from the original T1 W signals, including proton density, T2 * decay, and coil sensitivity. A recently proposed multidimensional integration (MDI) technique was incorporated in the aT1 W calculation for better signal‐to‐noise ratio (SNR) performance. For comparison between aT1 W and T1 W results, Monte Carlo noise analysis was performed via simulation and on scanned data, and region‐of‐interest (ROI) analysis and comparison was performed on the system phantom. For brain scans, the image contrast, noise behavior, and SNR of aT1 W images were compared with routine GRE and inversion‐recovery–based T1 W images. The proposed aT1 W method yielded saliently improved T1 contrasts (potentially > 30% higher contrast‐to‐noise ratio [CNR]) than routine GRE T1 W images. Good spatial homogeneity and signal consistency as well as high SNR/CNR were achieved in aT1 W images using the MDI technique. For contrast‐enhanced (CE) imaging, aT1 W offered stronger post‐CE contrast and better boundary delineation than T1 MPRAGE images while using a shorter scan time. Abstract : With routine steady state GRE acquisition, the proposed aT1W method offered significantly improved T1 contrasts comparable to IR‐based methods like MPRAGE.